Belonging: a meta-theme analysis of women’s community-making in group antenatal and postnatal care - Horn, Anna; Orgill, Marsha; Billings, Deborah L.; Slemming, Wiedaad; Van Damme, Astrid; Crone, Mathilde; Gwele, Malibongwe; Leister, Nathalie; Hindori-Mohangoo, Ashna D.; Beeckman, Katrien; Bradley, Susan; Hindori, Manodj P.; et al. (Frontiers in Public Health, 2025)
Health care systems are social institutions simulating microcosms of wider societies where unequal distribution of power and resources translate into inequities in health outcomes, experiences and access to services. Growing research on participatory women’s groups positively highlights the influence of group-based care on health and wellbeing for women, their infants, families and wider communities across different countries. With similarities in ethos and philosophies, group care combines relational, group-based facilitation and clinical care, uniquely offering an opportunity to examine the intersections of health and social care. With collated data from Group Care for the First 1000 Days (GC_1000), we conducted a qualitative meta-thematic analysis of women’s experiences of group antenatal and postnatal care in Belgium, Ghana, Kosovo, The Netherlands, South Africa, Suriname and The United Kingdom to better understand how and to what extent community-making engenders a sense of belonging amongst group care participants and how these experiences may address social well-being and health. Results from this analysis expose that women actively participate in community building in group care in three key ways: (1) Collective agreements, (2) Boundary setting and (3) Care Gestures, orchestrated via socio-spatial building embedded in key pillars of the model. This analysis also illustrates how a sense of belonging derived from group care can mobilise women to support and care for the wider community through communal building of health literacy which builds from individual to communal empowerment: (1) Individual Health, (2) Community Health, (3) Partner Involvement, (4) Social Care and (5) Including Wider Community in Group Care. This research study builds upon existing evidence from both group care and participatory women’s group literature, showcasing the potential of group-based care to holistically address women’s needs. This research further illustrates the ways women create a sense of belonging in the context of group care and highlights why belonging may be an integral component of the model’s facilitation of improved health and well-being for individuals as well as their wider communities. More research is needed to understand the link between belonging and community mobilisation in the context of group care and how it may address the needs of underserved communities.